2018
DOI: 10.1371/journal.pone.0194160
|View full text |Cite
|
Sign up to set email alerts
|

The stress response gene ATF3 is a direct target of the Wnt/β-catenin pathway and inhibits the invasion and migration of HCT116 human colorectal cancer cells

Abstract: Aberrant Wnt/β-catenin signaling is implicated in tumorigenesis and the progression of human colorectal cancers, and mutations in the components of the Wnt/β-catenin signaling pathway are observed in the majority of patients. Therefore, extensive studies on the Wnt signaling pathway and its target genes are crucial to understand the molecular events of tumorigenesis and develop an efficacious therapy. In this study, we showed that the stress response gene ATF3 is transcriptionally activated by the binding of β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 66 publications
(114 reference statements)
0
25
0
Order By: Relevance
“…It has been reported that the overexpression of Runx2 in osteoblasts downregulates the activity of the ATF3 promoter, suggesting that ATF3 may be a downstream factor of Runx2 [ 52 ]. ATF3 is transcriptionally activated by the binding of β-catenin and TCF4 to the redundant TCF4 site in the proximal promoter region of the ATF3 gene, indicating that ATF3 is a direct target of the β-catenin pathway [ 54 ]. In vivo experiments also confirmed that 152RM promoted the formation and mineralization of new bone in the bone defects of DBM-MSN/152RM scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the overexpression of Runx2 in osteoblasts downregulates the activity of the ATF3 promoter, suggesting that ATF3 may be a downstream factor of Runx2 [ 52 ]. ATF3 is transcriptionally activated by the binding of β-catenin and TCF4 to the redundant TCF4 site in the proximal promoter region of the ATF3 gene, indicating that ATF3 is a direct target of the β-catenin pathway [ 54 ]. In vivo experiments also confirmed that 152RM promoted the formation and mineralization of new bone in the bone defects of DBM-MSN/152RM scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the Wnt9/10c promotor had higher probability scores for ATF and ATF2/CREB, which act as activating transcription factors, the promotors of Wnt3 and Wnt7 had a higher binding probability for ATF3, which is known to act as a repressor (Fig. 6D) (Hai, 2006;Hai et al, 1999;Inoue et al, 2018;Katoh, 2018;Zhou et al, 2017). Interestingly, one consensus sequence of ATF3 was further predicted to be located in the repressor element of Hydra Wnt3 (Nakamura et al, 2011).…”
Section: A Mapk Network Modulates Wnt Signalingmentioning
confidence: 95%
“…MMPs and TIMPs have prominent roles in cancer invasion and metastasis. TIMPs, binding to MMPs at a 1:1 molar ratio, are able to block the access of substrates to the catalytic domain of endopeptidases and eventually inhibit the bioactivities of MMPs ( 20 ). Furthermore, increases in the MMP/TIMP ratio have been reported to affect invasion and metastasis, and are widely considered as a marker for cancer invasion ( 21 - 23 ).…”
Section: Resultsmentioning
confidence: 99%